Pengaruh Berbagai Dosis Bionetral Terhadap Penurunan Jumlah Lalat yang Hinggap Pada Sampah Organik Pasar - Ekhi Kharisma Prihangkasa; Adib Suyanto; Mohammad Mirza Fauzie (Sanitasi: Jurnal Kesehatan Lingkungan, 2013)
Organic waste which is yielded from market activities produce bad smell as a result of waste decomposition process. This continuing and sustaining unpleasant odor if are not well controlled can disturb the surrounding people’s activities and also become breeding places for various di-sease vectors such as fly. Bionetral is a product which can reduce the bad odor rise from the waste, and this study was aimed to understand the influence of various doses of this product in reducing the number of flies which are attracted to organic waste from traditional market, as well as to determine the most effective dose. The study was an experiment which employed pre test post test with control group design. The doses of Bionetral used were 35 ml, 40 ml, 45 ml and 50 ml for every 400 gr organic waste. The main procedure of the experiment consisted of observing and calculating the number of attracted flies before and after the organic waste sprayed by Bio-netral. With taken into account the decrease number of attracted flies which also occured in the control gorup, the one way Anova statistical test concluded that the dose differences of the product affected the number of attracted flies, and the consequent LSD statistical test found that the 50 ml/400 gr dose was the most effective in controlling the unpleasant odor and so that reducing the biggest number of flies which were perched to the waste.